1982
DOI: 10.1159/000299490
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Women with Significant Fear of Childbirth during Late Pregnancy

Abstract: An unselected, consecutive series of 139 third-trimester pregnant women was investigated concerning ‘fear of delivery’. Two methods to identify women with this sentiment were used independently and on the same occasion; i.e. a personal interview and a questionnaire including statements concerning ‘fear of childbirth’ to be affirmed or denied. The results obtained by the two methods were found to correspond well, i.e. much the same women who had verbally expressed significant fear of delivery during a personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 5 publications
4
56
0
1
Order By: Relevance
“…The samples investigated had previously been categorised independently by an assistant by means of a special questionnaire. By this procedure it was possible for the interviewer to be 'blind' with regard to the patient's group affiliation [Areskog et al, 1982b], Previous studies have demonstrated that patient samples made up with the questionnaire as the only selecting instrument are likely to contain both women admitting and not admitting to fear of delivery [Areskog et al, 1981;1982a], Real differences between women admitting and not admit ting fear are therefore likely to be more difficult to reveal, when such het erogeneous samples are compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples investigated had previously been categorised independently by an assistant by means of a special questionnaire. By this procedure it was possible for the interviewer to be 'blind' with regard to the patient's group affiliation [Areskog et al, 1982b], Previous studies have demonstrated that patient samples made up with the questionnaire as the only selecting instrument are likely to contain both women admitting and not admitting to fear of delivery [Areskog et al, 1981;1982a], Real differences between women admitting and not admit ting fear are therefore likely to be more difficult to reveal, when such het erogeneous samples are compared.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of this special questionnaire [Areskog et al, 1982a] and the further inclusion criteria used to create the two samples have been described previously [Areskog et al, 1982b].…”
Section: Patient Materialsmentioning
confidence: 99%
“…In Western countries about 6-15 % [1][2][3][4] of pregnant women fulfil the criteria for severe FOC, i.e. that the fear affects their daily life negatively [5].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Several studies have shown a connection between fear of childbirth and psychiatric disorders (such as depression, anxiety disorders, eating disorders, bipolar disorder), [6][7][8] but there are also contradictory results suggesting that only a small part of fear is related to general anxiety and depression 9 or that postpartum depression is not related to fear of vaginal delivery. 10 Previously, all studies have concentrated on symptoms of depression and anxiety during pregnancy [6][7][8][9] or they have excluded women with diagnosed psychiatric illnesses, 10 but the well-being of fearful women before and after pregnancy and childbirth has not been examined using large-scale registers.…”
Section: Introductionmentioning
confidence: 99%